2021
DOI: 10.1016/j.heliyon.2021.e08463
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical devices of stance in written academic English

Abstract: Stance is a feature of academic writing that refers to how writers interact and engage with their readers by means of linguistic devices. This study focuses on the grammatical devices-and semantic distinctions thereof-that are employed by academic writers of English to express stance in research article abstracts in the areas of applied linguistics (AL) and literature (L). To this end, a corpus of 120 research article abstracts (60 in the area of AL and another 60 in that of L) was built and analysed using SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…In this respect, Petchkij (2019) found that the modals as subcategories of hedge were the most frequently employed by Thai EFL students in the academic writing classroom. The result of this study is also related to that of Alghazo et al (2021), in which modals and semi-modals were mostly counted and increasingly contributed to applied linguistics than in the literature research article abstract. The reason was that the slippery nature of the applied linguistic subject is remarked by uncertainty and ambiguity.…”
Section: Discussionsupporting
confidence: 53%
“…In this respect, Petchkij (2019) found that the modals as subcategories of hedge were the most frequently employed by Thai EFL students in the academic writing classroom. The result of this study is also related to that of Alghazo et al (2021), in which modals and semi-modals were mostly counted and increasingly contributed to applied linguistics than in the literature research article abstract. The reason was that the slippery nature of the applied linguistic subject is remarked by uncertainty and ambiguity.…”
Section: Discussionsupporting
confidence: 53%
“…As noted earlier, engagement as an interactional metadiscourse feature has not yet received due attention in metadiscourse research, compared to other features of stance and voice (Alghazo et al, 2021 ). Engagement has often been examined in a subsidiary manner to stance (see Hyland, 2005 ; Alghazo et al, 2021 ; Herzuah, 2018 ; Abusalim et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it is noted that such competence leads the EFL students to writing barriers. The reason is because English grammar consists of comprehensive types which cannot be easily understood by the EFL students as beginner paper authors (Alghazo, Al Salem, Alrashdan, & Rabab'ah, 2021;Ma & Qian, 2020;Prćić, 2014). The authors are responsible for the quality of each sentence they write in a paper.…”
Section: Discussionmentioning
confidence: 99%